Circulating microRNAs in arrhythmogenic right ventricular cardiomyopathy with ventricular arrhythmia. Issue Volume 20:Issue FI 1(2018) (25th September 2017) - Yamada, Shinya; Hsiao, Ya-Wen; Chang, Shih-Lin; Lin, Yenn-Jiang; Lo, Li-Wei; Chung, Fa-Po; Chiang, Shuo-Ju; Hu, Yu-Feng; Tuan, Ta-Chuan; Chao, Tze-Fan; Liao, Jo-Nan; Lin, Chin-Yu; et al.
Abstract: Aims: MicroRNAs (miRNAs) have been implicated in cardiac diseases. This study aimed to characterize the circulating miRNAs in patients with arrhythmogenic right ventricular cardiomyopathy (ARVC) and correlate the miRNAs with the clinical outcomes of ARVC. Methods and results: This study included 62 patients with ventricular arrhythmia (VA): 28 patients (45%) had definite ARVC, 11 (18%) had borderline or possible ARVC, and 23 (37%) had idiopathic ventricular tachycardia (VT). In addition, 33 age- and sex-matched healthy subjects were enrolled as normal control subjects. The expression of selected miRNAs was analysed in all study subjects. The clinical outcomes of patients with definite ARVC after catheter ablation were further investigated. On the basis of the miRNA polymerase chain reaction array, we selected 11 miRNAs for analysis of their expression in the plasma of all subjects. Definite ARVC patients had significantly higher expression of circulating miR-144-3p, 145-5p, 185-5p, and 494 than the three other groups. Out of 25 definite ARVC patients who underwent radiofrequency catheter ablation, recurrent VA occurred in 8 patients (32%) during the follow-up period (45 ± 20 months). Definite ARVC patients with recurrent VA had a higher level of circulating miR-494 than did those without recurrence. Receiver operating characteristic analysis showed miR-494 to be a predictive factor of recurrent VA (area under the curve: 0.832). Conclusion: Plasma levels of miR-144-3p, 145-5p, 185-5p, and 494 were significantly elevated in definite ARVC patients with VA. An increased plasma level of miR-494 was associated with the recurrence of VA after ablation in definite ARVC patients.